Synthesis, Antimicrobial Activity, Structure-Activity Relationship, and Molecular Docking Studies of Indole Diketopiperazine Alkaloids - Jia, Bin; Ma, Yang-min; Liu, Bin; Chen, Pu; Hu, Yan; Zhang, Rui (Frontiers in Chemistry, 2019)
Strategies for the synthesis of indole diketopiperazine alkaloids (indole DKPs) have been described and involve three analogs of indole DKPs. The antimicrobial activity and structure-activity relationship (SAR) of 24 indole DKPs were explored. Compounds 3b and 3c were found to be the most active, with minimum inhibitory concentrations (MIC) values in the range of 0.94-3.87 μM (0.39-1.56 μg/mL) against the four tested bacteria (Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli). Furthermore, compounds 4a and 4b displayed broad-spectrum antimicrobial activity with MIC values of 1.10-36.9 μM (0.39-12.5 μg/mL) against all tested bacteria and plant pathogenic fungi (Colletotrichum gloeosporioides, Valsa mali, Alternaria alternata and Alternaria brassicae). According to the in silico study, compounds 3c showed significant binding affinity to the FabH protein from Escherichia coli, which has been identified as the key target enzyme of fatty acid synthesis (FAS) in bacteria. Therefore, these compounds are not only promising new antibacterial agents but also potential FabH inhibitors.